Distribution Characteristics of the Deep Geothermal Field in the Sichuan Basin and its Main Controlling Factors - Zhu, Chuanqing; Xu, Tong; Qiu, Nansheng; Chen, Tiange; Xu, Ming; Ding, Rui (Frontiers in Earth Science, 2022)
Geothermal energy and petroleum are two resources that coexist in sedimentary basins, and both them are closely related to temperature. Based on the surface heat flow and the rock thermal properties, this work calculated the deep geothermal fields in the Sichuan Basin, evaluated the temperature distribution characteristics and discussed the primary influencing factors on the geothermal state of the basin. The temperature distribution map of the Sichuan Basin for depths of 4000–9000 m presented the central and southern areas are characterized by relatively high temperatures while the northwestern and northeastern areas are characterized by low temperatures. At 7000 m, the temperatures in the central and southern areas were above 180°C, which is the threshold temperature for hot dry rock (HDR), while the temperatures in the northwestern and northeastern areas were below 160°C, which is close to the lower limit for oil crude oil cracking. The central and southern areas are favorite zones for the exploration of geothermal energy, conversely, the relatively low temperatures in the northern, northwestern, and eastern areas are conducive to the presence of oil and gas. The unevenly distribution of geothermal field were controlled by the thicknesses of sedimentary layer and the crust, which indicates the lithosphere flexure and thickening caused by compression and depression, rapid deposition in the foreland depressions. The results can provide geothermal understandings for the exploration and development of the oil, gas, and geothermal resources and could serve as a reference for geodynamic studies in the Sichuan Basin.